Job satisfaction among academic and administrative staff in Universiti Malaysia Sarawak - Lim, Jia Mien (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The aims of this study were to investigate the levels of job satisfaction among academic and administrative staff in UNIMAS and also differences in job satisfaction based on demographic characteristics such as position (academic staff or administrative staff), gender and discipline. The dimensions of job satisfaction included in this study were promotion, supervision, work itself, colleagues, work environment and pay and benefits. A cross-sectional survey research using questionnaire was conducted at eight faculties in UNIMAS. Fifty-nine sets of valid questionnaires were returned from six faculties and used for data analysis. Independent t-tests were used to investigate the academic and administrative staff differences, gender differences and discipline differences in the levels of job satisfaction. The findings showed that the academic and administrative staff were satisfied with the six dimensions of job satisfaction in this study. There were only differences in the levels of job satisfaction in the dimension of "work itself' between academic and administrative staff. Hence, it is recommended that the University should be concerned with the job satisfaction of the academic and administrative staff. The management should redesign the job task of the staff to meet the preference of the staff to increase the levels of job satisfaction among academic and administrative staff.